2009
DOI: 10.1021/jp900267t
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Poly(o-methoxyaniline) Hollow Microspheres

Abstract: Hollow microspheres of poly(o-methoxyaniline) (POMA) were prepared in a solution of p-toluenesulfonic acid (p-TSA) using ammonium persulfate (APS) as oxidant. The morphology of the final polymers was characterized by scanning electron microscopy and transmission electron microscopy techniques. The molecular structure and electrical properties of the products were investigated using a range of spectroscopic methods. The mechanism of nanostructure formation was studied in the light of the chemical nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…Formation mechanisms of PoPD hollow structures have been proposed according to our previous literatures [36][37][38][39][40], where monomer droplets are considered as template for the generation of hollow structures while diffusion flux of monomers during polymerization processes results in the formation of hole in each surface. The monomer droplets as proposed by our group have also been confirmed by others [42]. It can be reported that besides hollow structures, solid structures and other structures are seldom seen, which proves high uniformity of products.…”
Section: Morphology and Formation Mechanisms Of Popd Hollow And Solidsupporting
confidence: 84%
“…Formation mechanisms of PoPD hollow structures have been proposed according to our previous literatures [36][37][38][39][40], where monomer droplets are considered as template for the generation of hollow structures while diffusion flux of monomers during polymerization processes results in the formation of hole in each surface. The monomer droplets as proposed by our group have also been confirmed by others [42]. It can be reported that besides hollow structures, solid structures and other structures are seldom seen, which proves high uniformity of products.…”
Section: Morphology and Formation Mechanisms Of Popd Hollow And Solidsupporting
confidence: 84%
“…Spheres with hollow interiors play an important role in microencapsulation and have been used in medical, biological, pharmaceutical and industrial applications (Hu et al 2007;Bai et al 2009;Xiao et al 2009;Yan et al 2009;Zhang et al 2009). Both organic and inorganic materials have been investigated to manufacture new and smart hollow microspheres and offer advantages such as low effective density, large internal 'payload' space and high specific surface area (Lou et al 2008;Shiomi et al 2009;Zimmermann et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2 shows the FTIR spectra of the neat BAPBACP monomer at different cure temperatures. 25 Furthermore, the intensity of the absorption band at 1500 cm À1 , assigned to 1,2,4-trisubstituted benzene, had little change during the curing, indicating that the benzene ring in the structure of the BAPBACP monomer did not alter during the ring-opening process. At the initial reaction stage (BAPBACP curve in Fig.…”
Section: Ftir Analysis Of Bapbacp Monomer Systemsmentioning
confidence: 97%